2020
DOI: 10.2196/21418
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Insights Into US Mental Health During the COVID-19 Pandemic: Longitudinal Analysis of Twitter Data

Abstract: Background The COVID-19 pandemic led to unprecedented mitigation efforts that disrupted the daily lives of millions. Beyond the general health repercussions of the pandemic itself, these measures also present a challenge to the world’s mental health and health care systems. Considering that traditional survey methods are time-consuming and expensive, we need timely and proactive data sources to respond to the rapidly evolving effects of health policy on our population’s mental health. Many people i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
151
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(209 citation statements)
references
References 42 publications
10
151
1
2
Order By: Relevance
“…However, the results regarding information-searching also highlight the potential downsides of internet use. This accords with a recent study [ 27 ] showing generally increased use of social media in 2020, which for some served as a coping mechanism to combat isolation, but caused deleterious effects on mental health in others: the role of greater exposure to crisis-related news was important in explaining this. Thus, while the current findings support the suggestion that addressing the “digital divide” and implementing strategies that facilitate internet use amongst older people might benefit mental health and counter isolation during the crisis [ 5 ], some forms of information access might not be beneficial.…”
Section: Discussionsupporting
confidence: 87%
“…However, the results regarding information-searching also highlight the potential downsides of internet use. This accords with a recent study [ 27 ] showing generally increased use of social media in 2020, which for some served as a coping mechanism to combat isolation, but caused deleterious effects on mental health in others: the role of greater exposure to crisis-related news was important in explaining this. Thus, while the current findings support the suggestion that addressing the “digital divide” and implementing strategies that facilitate internet use amongst older people might benefit mental health and counter isolation during the crisis [ 5 ], some forms of information access might not be beneficial.…”
Section: Discussionsupporting
confidence: 87%
“…We also found that higher levels of resilient coping and hope were associated with reduced anxiety and depression symptoms, highlighting the potential protective effects of resilient coping, positive psychosocial strength, and proactive behaviors during public health crises [ 18 , 19 ]. Our results suggest that interventions that include strategies to enhance resilient coping and build hope such as community-wide mindfulness-based stress reduction training [ 34 ], web-based programs to promote positive psychology [ 35 ] and use of social media to enhance social connectedness and support [ 36 ], may be beneficial and help prevent mental health symptoms [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future research should include more representative samples and multiple follow-ups to further our understanding of the short- and long-term effects of the COVID-19 lockdown on the mental health of the global population. Future studies should also develop population-based, culturally appropriate interventions that promote positive mental health and mitigate risk exposures in order to reduce the mental health burden during this and other global emergencies [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various world leaders have utilised the platform to inform, boost morale and prompt political discussion [ 36 ]. Given such uptake, it is not surprising that health measures trended in the Twittersphere [ 37 – 39 ]. This study documents several health risk measures communicated, often in combination.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern could reflect citizens’ desire for official guidance at the outset of the pandemic when everything was in a state of uncertainty. The shift towards individual voices from March onwards aligns with the stay-at-home mandates when individual social media use generally increased [ 39 ]. The prominence of individual voices highlights the importance of citizens (particularly influencers) sharing health messages among their networks, enabling health messages to reach broader segments of the population and promoting solidarity and inclusiveness.…”
Section: Discussionmentioning
confidence: 99%